High-fidelity simulation training for nasal bridle placement with a 3D printed model - Yu-Hui Huang, MD, MS; David Nascene, MD; Benjamin Spilseth, MD, MBA; Jeffrey A. Chuy, MD (Annals of 3D Printed Medicine, 2023)
Background: Nasal bridles help prevent nasoenteric feeding tube dislodgement. If placed incorrectly, nasal bridles can cause injury, epistaxis, skin ulceration, or failure to prevent dislodgment. Training is frequently performed on patients, which can lead to discomfort or complications. To improve training prior to placing nasal bridles in patients, we utilized an anatomically accurate 3D printed simulator for nasal bridle placement training. Methods: The model was modified from a nasopharyngeal swab simulator by BONE 3D, which was developed from imaging data through segmentation, computer-aided design, and 3D printing. Eighteen radiology residents and 3 medical students received a pre-test covering the anatomical knowledge and technique relevant to nasal bridle placement followed by a training session using the model. After training, participants provided feedback on the impact of training with the model on anatomical knowledge, hands-on skills, and confidence via a post-test using a 5-point Likert scale [from 1 (not beneficial/confident) to 5 (extremely beneficial/ confident)]. Results: Twenty participants completed both pre- and post-tests. The group performed significantly better on the post-test (4.8 ± 0.52) than the pre-test (2.6 ± 1.64), and the intervention demonstrated a large effect on knowledge (p < 0.0001; d = 1.82) and confidence level (p < 0.0001, d = 2.45) with mean magnitude of improvement of 2.3 out of 5 points. All respondents requested the 3D printed model be offered in formal training. Conclusions: An anatomically accurate 3D printed model is a feasible and acceptable training aid with the potential to facilitate novice knowledge, proficiency, and confidence for nasal bridle placement.